Distraction chondroneogenesis on rabbit's ear cartilage [Tavşan kulak ki{dotless}ki{dotless}rdag̀i{dotless}nda distraksiyon kondroneogenezisi] - DURMUŞ KOCAASLAN, FATMA NİHAL; TÜRKÖZ, HÜSEYİN KEMAL; ÇELEBİLER, ÖZHAN BEKİR (My University, 2013)
Objective: Application of distraction is an alternative to bone graft or fap operations for repairing bone defects. Bone can be extended in width and length without using a new donor area. Operation time is shortened and failures are reduced without any concern about graft or fap loss. However, there are no distraction methods known for generating new cartilage as an alternative to graft or fap applications in repairs of cartilage defects This experimental study was planned to determine whether or not chondroneogenesis can be obtained via application of distraction. Methods: Fourteen New Zealand rabbits were used in this study. Distractions at a rate of 0.50 mm/day, 0.25 mm/day and 0.25 mm on alternate days were applied on 3 rabbits consecutively and the ideal distraction rate was determined as 0.25 mm once every two days. On alternate days 0.25 mm of distraction was applied for two months aiming to generate 7.5 mm of new cartilage. Results: In the rabbits in which 0.25 mm of distraction on alternate days had been applied, regular new cartilage formation was observed. Conclusions: According to these findings, the slow metabolic rate of avascular cartilage tissue affects distraction rates and rhythms. However, by applying distraction and taking advantage of the regenerative capacity of the perichondrium, it is possible to generate new and regular chondrocytes and extend the cartilage.
Keywords: Cartilage; Distraction; Rabbit